Sporting lives metaphor and myth in American sports autobiographies - Pipkin, James W., 1944- (Sports and American culture series., 2008)
"Examines autobiographies by athletes such as Wilt Chamberlain, Babe Ruth, Martina Navratilova, and Dennis Rodman, and analyzes common themes and recurring patterns in the accounts of their lives and sporting experiences"--Provided by publisher.